Revisions to the Financial Action Task Force (FATF) Standard : Information Note to the Executive Board. (Policy Papers; Policy Paper ;, 2012)
The purpose of this note is to inform the Executive Board of the amendments made to the standard on anti-money laundering and combating the financing of terrorism (AML/CFT). The Financial Action Task Force (FATF)-the standard setter for AML/CFT-adopted on February 16, 2012 a revised standard, now entitled the 'International Standards on Combating Money Laundering and the Financing of Terrorism and Proliferation: the FATF Recommendations.'.